2015
DOI: 10.3389/fmicb.2015.01168
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and spatial patterns of microbial diversity along a trophic gradient in the interconnected lakes of the Osterseen Lake District, Bavaria

Abstract: The Osterseen Lake District in Bavaria consists of 19 small interconnected lakes that exhibit a pronounced trophic gradient from eutrophic to oligotrophic. It therefore presents a unique model system to address ecological questions regarding niche adaptation and Baas Becking's long standing hypothesis of “everything is everywhere, but the environment selects.” Here, we present the first assessment of the microbial diversity in these lakes. We sampled the lakes in August and December and used 454 pyrosequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 49 publications
4
31
0
Order By: Relevance
“…Thanks to the development of next generation sequencing (NGS), we can present the biodiversity of the picoeukaryotes at a finer scale. It has been reported that investigations of microbial community on the basis of changes in highly abundant taxa or only at higher taxonomic levels may mask distinct patterns in microbial distribution (Zwirglmaier et al ., ). At the phylum or class levels, little variation of the picoeukaryotes community was unveiled in our samples (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thanks to the development of next generation sequencing (NGS), we can present the biodiversity of the picoeukaryotes at a finer scale. It has been reported that investigations of microbial community on the basis of changes in highly abundant taxa or only at higher taxonomic levels may mask distinct patterns in microbial distribution (Zwirglmaier et al ., ). At the phylum or class levels, little variation of the picoeukaryotes community was unveiled in our samples (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The quality filtering step eliminated about 17% of all valid merged sequences. Lastly, the remaining reads were pooled together, dereplicated and clustered to define operational taxonomic units (OTUs) using cluster_otus algorithm at a 97% similarity threshold (Zwirglmaier et al, 2015). After removing the singletons (OTUs with only one read), 1580 OTUs were defined.…”
Section: Sequence Processing and Analysismentioning
confidence: 99%
“…UPGMA clustering of bacterial communities indicated an apparent spatial variation in bacterial communities in the lake and the streams. In general, physicochemical parameters, nutrients, and nutrient ratios could drive bacterial communities in freshwater ecosystems [34,[47][48][49][50][51]. Our results demonstrated that N-factor (NO 3 − ) (7%) and the interaction of multiple factors, including physicochemical-factor, N-factor, P-factor, and C-factor, drove the bacterial community structure on stream biofilms (Figure 7f).…”
Section: Discussionmentioning
confidence: 66%
“…These results may suggest that MC-degrading bacterioplankton community diversity may increase with trophic status (from oligo to fully eutrophic) of freshwater lakes. However, as indicated by [67][68][69], the relationship between trophic status and community diversity of bacterioplankton is not so clear-cut, as other studies have reported contradictory trends [68,69]. Furthermore, it is still unclear how diversity may influence MC biodegradation kinetics in the environment as the temporal stability of these bacterioplankton communities is relatively unknown (i.e., do they achieve a relative steady state?).…”
Section: Discussionmentioning
confidence: 99%